Diagnostic and surgical management of primary central nervous system angioleiomyoma: A case report and literature review - Rubiu, Emanuele; La Corte, Emanuele; Bonomo, Giulio; Restelli, Francesco; Falco, Jacopo; Mazzapicchi, Elio; Broggi, Morgan; Schiariti, Marco Paolo; Pollo, Bianca; Pinzi, Valentina; Bruzzone, Maria Grazia; Di Meco, Francesco; et al. (Frontiers in Oncology, 2022)
Angioleiomyoma (ALM) is a benign smooth muscle neoplasm that mainly occurs in lower extremities subcutaneous tissue and generally affects middle-aged adults. This tumor histotype may rarely localize intracranially, although only a few cases have been described in the literature. We report a case of intracranial ALM, whose differential diagnosis has been particularly challenging, and firstly provide a comprehensive radiological and intra-operative evaluation of a such rare entity. This represents also the first report of the use of intraoperative confocal microscopy in ALM and the first documented short-term recurrence. At this regard, a systematic literature review has been conducted with the aim of presenting the major clinical and diagnostic features along with the proposed therapeutic strategies.